Bridging gaps: Assistive technology empowering working adults with disabilities for sustainable development - Hamedani, Sharareh Shahidi; Aslam, Sarfraz; Hamedani, Shervin Shahidi; Razzaqi, Hasan (International Journal of Innovative Research and Scientific Studies, 2025)
Worldwide, an estimated 1.3 billion people of the global population experience significant disabilities. The recent UN Flagship Report on Disability and Sustainable Development Goals emphasizes that the entire achievement of the UN Agenda 2030 requires the active involvement of all individuals, including those with disabilities. The current study explored how Assistive Technology (AT) integration in workplaces contributes to achieving SDG 4 for working adults seeking continuous professional development and the challenges and opportunities in implementing AT in workplaces to support SDG 10. Data were collected from two countries (Malaysia and Canada) using semi-structured interviews. Braun and Clarke’s six steps were used to analyze data. Based on the responses, two primary and eleven sub-themes were generated. AT plays a crucial role in developing essential skills in the workplace. It is a transformative resource supporting ongoing professional growth for working adults with disabilities. There are many obstacles to successfully adopting and using AT, including organizational, cultural, technical, and financial ones. Developing partnerships among employers, policymakers, and developers of AT is vital for the sustainable use of these resources.